Effects of vegetation and physicochemical properties on solute transport in reclaimed soil at an opencast coal mine site on the Loess Plateau, China - Zhen, Qing; Ma, Wenmei; Li, Mingming; He, Honghua; Zhang, Xingchang; Wang, Yi (Catena (Giessen), 2015)
Mine soils are often polluted and degraded. The objectives of this study were to assess the effects of soil properties and vegetation on soil solute transport in reclaimed soil at an opencast coal mine site on the Loess Plateau. Four reclaimed areas with different vegetation types were selected for the analysis of physical and chemical properties. The miscible displacement technique was used to obtain the breakthrough curves (BTCs) of NO3− ion transport in undisturbed soil columns, which were taken from the soil profiles of the different sites. The chemical properties, such as total N, P, K and SOM, exhibited low contents, and the soil physicochemical properties showed high heterogeneity between different depths and different reclaimed areas. The structural stability index was less than 5%. The initial and entire penetration times were longer in the deeper layers than in the top layer. The BTCs of NO3− were fitted well by the deterministic equilibrium convection dispersion equation (CDE) model. Preferential flow and transport were found in the soil columns. The reclaimed soil had poor structure, and planting vegetation improved the physiochemical properties of the soil. The soil solute transport parameters exhibited high heterogeneity between different samples and were significantly correlated with soil bulk density and soil texture, which were highly influenced by vegetation and human activities. In the process of land reclamation, increasing the bulk density and selecting fine-textured soils could reduce the average soil pore water velocity and the dispersivity coefficient, thereby extending the solute penetration time. •Planting vegetation could improve the reclaimed soil properties.•Preferential flow was ubiquitous in the reclaimed soils.•The CDE model fitted the solute transport processes well.•Fine textures and appropriate densities should be given more consideration during the process of soil reclamation.